Religious Enlightenment in the eighteenth-century Nordic countries - Ljungberg, Johannes; Sidenvall, Erik (Manchester University Press, 2024)
This volume explores how changes that we tend to associate with the Enlightenment were intertwined with practices and rationales within Lutheran confessional culture in the two Nordic states during the long eighteenth century. It does so by examining several well-rehearsed topics of Enlightenment studies. Scientific novelties, realized policies, and reading as well as printing practices are all themes that return in this book; here they are understood in relation to the various modes and rationales of confessional culture. More precisely, all the contributions to the present volume deal with ideas related to three 'R's: reason, rationalism and reform. The eighteenth century encountered in this volume is not only a story of clashes and conflicts. Reason is not necessarily seen as replacing religious belief, nor is rationalism viewed as opposed to reasonings occurring within religious policies or institutions. Evidence of reform may in some cases be interpreted as expressions of Enlightenment; but there is a recurring echo of previous religious transformations and measures promoting renewal, not least in relation to the historical experience of the Lutheran Reformation. Therefore, the writers have chosen to place the notion of 'religious Enlightenment' at the core of this book. All the various chapters proceed from this fundamental conception in their explorations of ideas and practices that were embedded in a landscape shaped by both reason and orthodoxy.